Present and Future Human Emissions of Rotavirus and Escherichia coli to Uganda's Surface Waters. Issue 5 (1st September 2018) - Okaali, Daniel A.; Hofstra, Nynke
Abstract : Rotavirus (RV) and diarrheagenic Escherichia coli are waterborne pathogens commonly causing diarrhea in children below five years old worldwide. Our study is a first step toward a loads–concentrations–risk modeling and scenario analysis framework. We analyzed current and future human RV and indicator E. coli (EC) emissions from sanitation facilities to surface waters in Uganda using two process‐based models. Emissions were estimated for the baseline year 2015 and for three scenarios in 2030 using population, excretion rates, sanitation types, and wastewater treatment. The first model is a downscaled GloWPa‐Rota H1 version, producing emissions at a 1‐km 2 resolution. The second model is newly developed for Kampala and adds emissions from pit latrines and septic tanks excluded in the first model. The scenarios Business as Usual, Industrious, and Low Emissions reflect government prospects in sanitation coverage and wastewater treatment. For the first model, 6.14 × 10 14 RV particles d −1 and 1.31 × 10 12 EC colony‐forming units (CFU) d −1 are emitted to surface waters in 2015. The RV emissions are expected to increase in 2030 by 75% for Business as Usual and 212% for Industrious and decrease by 58% in Low Emissions. Emissions from the second model are higher for Kampala than in the first model, at 3.74 × 10 14 vs. 5.95 × 10 13 RV particles d −1 and 8.18 × 10 11 vs. 1.75 × 10 11 EC CFU d −1 in 2015, most of which come from the onsite‐not‐contained category. Simulated emissions for Kampala show the importance of including onsite sanitation in our modeling. Our study is replicable in other locations and helps identify key emission sources, their hotspots, and the importance of wastewater treatment. The scenarios can guide future sanitation safety planning. Core Ideas: Rotavirus and E. coli emissions from sanitation facilities reach surface water. Using modeling and scenario analysis, we simulated these emissions for Uganda. High‐emission areas are Kampala and other urban areas. A new model including onsite sanitation shows higher emissions in Kampala. Future emissions are reducible through sanitation planning.